Consultoría para identificación y elaboración del mapa de actores y relaciones de 3 cuencas - Manrique, F.B.; Serrano, N.R. (CONDESAN, 2011)
Consulting services for the identification of actors and studies on knowledge, attitudes and practices for the purpose of preparing a map of stakeholders and relationships between them in three selected basins.